Effect of replacing corn with soy hulls on nutrient digestibility of growing pigs - Oh, Han Jin (J Anim Sci Technol, 2020)
The objective of this study was to determine the effect of replacing corn with soy hulls on nutrient digestibility of growing pigs. Three experimental diets were tested using a 3 × 3 Latin square design using three barrows per group (Landrace × Yorkshire × Duroc, average initial body weight of 36.9 ± 4.0 kg) in individual metabolic cages. The dietary treatments were the control (CON) basal diet (corn-soybean meal based diet), whereas in the test diets, soy hulls were included at 5% (H1), 10% (H2), gradually replacing corn. The daily feed allowance was adjusted to 2.7 times the maintenance requirement for digestible energy (DE) (2.7 × 110 kcal of DE/kg BW(0.75)). Intake of crude fiber (CF) was different among treatments (p < 0.05). Pigs fed with H2 diet excreted higher concentrations of dry matter (DM), and CF than pigs fed with H1 diet and basal diet (p < 0.05). Pigs fed with H1 and H2 diets excreted higher concentrations of crude protein (CP) than pigs fed with CON diet (p < 0.05). The apparent total tract digestibility (ATTD) of CF from H1 and H2 diets were higher than CON diet (p < 0.05). Pigs fed with H2 diets were significantly lower (p < 0.05) the ATTD of CP than the pigs fed with CON and H1 diets. The current data suggest that 10% inclusion soy hulls can slightly decrease CP digestibility. However, soy hulls considerably increased CF digestibility.It is concluded that 5% soy hulls may be a usable alternative to corn in growing pig diets.